Relationship between Number and Order of Children with Exclusive Breastfeeding Practices in Surakarta - Vivienne Tjung; Husnia Auliyatul Umma; Jarot Subandono (Fakultas Kedokteran UNS, 2021)
Introduction: Exclusive breast milk is breastfeeding for six months to babies, without providing other foods and drinks. Breastfeeding for up to 6 months is recommended by various health organizations, including the Ministry of Health. In Indonesia, exclusive breastfeeding is still low, even though the benefits of breastfeeding are numerous. Various studies that have been conducted have shown different results regarding the relationship between the number and sequence of children with breastfeeding practices. This study aimed to determine the relationship between the number of children and the order of the children with the practice of exclusive breastfeeding in SurakartaMethods: This study was an analytic observational study with a cross-sectional study design. The research sample was determined by random sampling of mothers registered at the Penumping Health Center. The research sample consisted of 50 people who have children aged 1-5 years. Assessment of completeness of breastfeeding was measured using a questionnaire. Data were analyzed using bivariate analysis techniques using chi-square and multivariate logistic regression.Results and discussions: From 47 subjects studied with the bivariate analysis technique using the chi square between the number of children and the order of children with exclusive breastfeeding practice, the results were less significant, p = 0.724 and p = 0.401.Conclusion: There was no significant relationship between the number of children and the order of children with the practice of exclusive breastfeeding in Surakarta.Keywords: Exclusive breastfeeding, number of children, order of children.